Sensitivity and specificity of pulse oximetry to detect congenital heart disease in newborns - Berlanga Bolado, Oscar Manuel; Rivera Vázquez, Patricia; Martínez Padrón, Hadassa Yuef (Horizonte Sanitario, 2023)
Objective: To determine the sensitivity and specificity of pulse oximetry to detect congenital heart disease in healthy newborns in rooming-in. Material and methods: The study is multicenter, prospective and cross-sectional, evaluating patients from the Regional Hospital of High Specialty "Bicentenario 2010" and the General Hospital “Dr. Norberto Treviño Zapata”, in the city of Victoria Tamaulipas, in a period from march 2015 to March 2017. Pulse oximetry was determined in healthy newborns before hospital discharge. Results: 511 newborns were studied. The sensitivity detected was 88.89% and a specificity of 99.80%. Conclusion: Congenital heart disease in healthy newborns in rooming-in can be determined by pre- and post-ductal pulse oximetry. Key words: Pulse oximetry; Cardiopathy; Newborn.